A New CFD Approach to Predict Condensation Heat Transfer Coefficient of Steam Over a Horizontal Tube Using Apparent Heat Capacity Method - Alfarawi, Suliman; Omar, Hossin; Elburki, Aynoor (Scientific Journal of University of Benghazi, 2025)
The present research paper aims to numerically solve fluid flow and heat transfer equation of a condensing steam over a single horizontal tube using computational fluid dynamics (CFD). The apparent heat capacity method is adopted in the current analysis which allows for the computation of a single-phase flow equation with an implicit capturing of the phase change interface between the vapor and liquid phases. A single energy equation is solved with effective material properties for the two phases based on the phase change temperature and the latent heat for the state change. The predicted heat transfer coefficient at different saturation temperatures [60, 80, 100 and 120 ºC] were initially compared to the results obtained from the well-known Nusselt analogy for laminar film condensation. It was found that the predicted heat transfer coefficient of 10429 W/m2. K at 60 ºC was 2% lower than that of Nusselt film analogy. While the predicted heat transfer coefficient of 11854 W/m2. K at 120 ºC was 18% than that of Nusselt film analogy. Also, the results revealed that the heat transfer coefficient is merely dependent on the cross-flow velocity of the vapor and hence the vapor shear.